189k views
1 vote
How to do step by step this

How to do step by step this-example-1

2 Answers

4 votes
❇First solve the terms in ( ) bracket:
↪1/4-{2/5+[1/3-(3×2-7)/2-1/4]-2/15}
= 1/4-{2/5+[1/3-(-1)/2-1/4]-2/15}
= 1/4-{2/5+[1/3+1/2-1/4]-2/15}

❇ Now solve the arithmetic terms in [ ] bracket...well by rule { } needs to be solved first but here { } has replaced the position of [ ] bracket.
= 1/4-{2/5+[1×4+1×6-1×3]/12-2/15}
= 1/4-{2/5+[4+6-3]/12-2/15}
= 1/4-{2/5+[10-3]/12-2/15}
❇Now solve arithmetic terms in { }
= 1/4-{2/5+7/12-2/15}
= 1/4-{2×12+7×5-2×4}/60
=1/4-{24+35-8}/60
=1/4-{59-8}/60
=1/4-51/60
=(1×15-51 )/60
don't get confused here that I placed ( )
=-36/60
=-3/5

❇NOTE:
▶Solve step by step by following rules:
1) First solve ( ) bracket (if any) then { } and then [ ] bracket

2) You must solve in this order
DMAS Division, Multiplication,Addition and then subtraction throughout the simplification process.
User TongChen
by
4.9k points
2 votes

Answer:

1/4 - (2/5 + (1/3 - (3 - 7/2) - 1/4) - 2/15)

= 1/4 - (2/5 + (1/3 - (6/2 - 7/2) - 1/4) - 2/15)

= 1/4 - (2/5 + (1/3 - (-1/2) - 1/4) - 2/15)

= 1/4 - (2/5 + (1/3 + 1/2 - 1/4) - 2/15)

= 1/4 - (2/5 + (4/12 + 6/12 - 3/12) - 2/15)

= 1/4 - (2/5 + (7/12) - 2/15)

= 1/4 - (2/5 + 7/12 - 2/15)

= 1/4 - (24/60 + 35/60 - 8/60)

= 1/4 - (51/60)

= 15/60 - 51/60

= -36/60

= -3/5

User Protheus
by
5.0k points